2022
DOI: 10.15282/ijame.19.1.2022.09.0728
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison Between Predictive Functional Control and PID Algorithms for Automobile Cruise Control System

Abstract: This work presents a performance comparison between a Predictive Functional Control (PFC) and a traditional Proportional Integral Derivative (PID) controller specifically for a cruise control application. The tuning efficacy, constraints handling, and disturbance rejection features of both controllers are analysed by comparing their closed-loop response. A simplified nonlinear vehicle longitudinal dynamics model is derived and utilised as a plant to simulate the control response from a real car. For a fair com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In general, the inputs to the system will be the pedal pressure from the throttle and brake, while the output of interest will be velocity. In a traditional cruise control system, the https://doi.org/10.31436/iiumej.v24i1.2341 braking effect is not considered, thus the standard kinetic vehicle longitudinal model can be used straight away to derive the control law of PFC as presented in [18]. However, the ACC system needs braking input as well to keep the safe distancing with a lead vehicle.…”
Section: Vehicle Longitudinal Dynamics Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the inputs to the system will be the pedal pressure from the throttle and brake, while the output of interest will be velocity. In a traditional cruise control system, the https://doi.org/10.31436/iiumej.v24i1.2341 braking effect is not considered, thus the standard kinetic vehicle longitudinal model can be used straight away to derive the control law of PFC as presented in [18]. However, the ACC system needs braking input as well to keep the safe distancing with a lead vehicle.…”
Section: Vehicle Longitudinal Dynamics Modellingmentioning
confidence: 99%
“…However, the ACC system needs braking input as well to keep the safe distancing with a lead vehicle. If a full kinetic modelling is used to derive the control law as in [18], the constraint implementation will be quite complicated especially if it is designed for full range dynamic operation where the nonlinearities will be very high due to the changing gear ratio and coefficient of friction between road and tire [2]. Thus, a hierarchal control strategy is often proposed in the literature [5,6] as shown in Fig.…”
Section: Vehicle Longitudinal Dynamics Modellingmentioning
confidence: 99%
“…Indeed, many efforts are proposed to reduce the computation load of MPC either by modifying the algorithm or the control structure [16]. Several authors have demonstrated by utilizing the Laguerre function in the control law, where a large control horizon can be represented using a smaller horizon to reduce the computation load [9]. Nevertheless, an additional tuning parameter is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, several works have proposed using Predictive Functional Control (PFC), a simplified MPC subvariant, to design an ACC system [9][10]. PFC uses a similar concept to MPC, except that it minimizes a single target error with direct inversion of equality between target trajectory and output prediction at a specific coincidence horizon instead of using a quadratic cost function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation